1985
DOI: 10.7863/jum.1985.4.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of neck masses in children.

Abstract: Neck masses in children are a frequent occurrence and in some instances create a diagnostic dilemma for the clinician. The authors' two-year experience using ultrasonography in the evaluation of 34 children with neck masses is reviewed. Twenty-two patients had lesions arising outside the thyroid gland; 12 lesions arose from the thyroid gland. Ultrasonography proved to be an accurate imaging modality for localizing the mass and demonstrating its relationship to the thyroid gland, trachea, and major neck vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 3 publications
0
16
1
Order By: Relevance
“…Sonognaphy has proved useful in imaging neck masses [1][2][3][4], but its use in children has not been extensively reported The most common midline lesion of the neck in a child is a thyroglossal remnant [5]. Thynoglossal duct cysts, which present as midline on slightly lateral to midline cystic masses, have a characteristic sonographic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Sonognaphy has proved useful in imaging neck masses [1][2][3][4], but its use in children has not been extensively reported The most common midline lesion of the neck in a child is a thyroglossal remnant [5]. Thynoglossal duct cysts, which present as midline on slightly lateral to midline cystic masses, have a characteristic sonographic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The typical sonognaphic appearance of a TDC has been described as an anechoic, well-circumscribed cyst with increased through transmission [2][3][4]. …”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown sonognaphy to be useful in evaluating abnormalities of the neck in children [2][3][4]. On the basis of these data, the sonognaphic appearance ofthe typicalTDC has been described as a cystic midline mass, usually atthe level ofthe hyoid bone.…”
Section: Ajr 1994;163:1475-1477mentioning
confidence: 99%
See 1 more Smart Citation
“…However, earlier studies in children have shown that most are not simple cysts but instead are either homogeneous or heterogeneous complex hypoechoic lesions 55 .…”
Section: Sonographmentioning
confidence: 99%